Prevalence of ESBL-producing Enterobacteriaceae in paediatric urinary tract infections: A systematic review and meta-analysis. Issue 6 (December 2016) - Flokas, Myrto Eleni; Detsis, Marios; Alevizakos, Michail; Mylonakis, Eleftherios
Summary: Objectives: We aimed to evaluate the prevalence of paediatric urinary tract infections (UTIs) caused by extended spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE), identify predisposing factors and examine their effect on the length of hospital stay (LOS). Methods: For this systematic review and meta-analysis, we searched the PubMed and EMBASE databases for studies that provide data on the rate of ESBL-PE among paediatric UTIs. Results: Out of 1828 non-duplicate citations, 16 studies reporting a total of 7374 cases of UTI were included. The prevalence of ESBL-PE was 14% [(95%CI 8, 21)]. Vesicoureteral reflux (VUR) [OR = 2.79, (95%CI 1.39, 5.58)], history of UTI [OR = 2.89 (95%CI 1.78, 4.68)] and recent antibiotic use [OR = 3.92, (95%CI 1.76, 8.7)] were identified as risk factors. The LOS was significantly longer among children infected with ESBL-PE, compared to those infected with other uropathogens. [SMD = 0.88, (95%CI 0.40, 1.35)]. Conclusions: In the paediatric population, 1 out of 7 UTIs are caused by ESBL-PE. Patients with VUR, previous UTI or recent antibiotic use constitute a high risk group and these pathogens are associated with increased LOS. The significant incidence of ESBL-PE in this population should be taken into consideration in the development of empiric treatment protocols and antibiotic stewardship programmes, especially in high-prevalence areas. Highlights: 14% of paediatric UTIs are caused by ESBL-producing Enterobacteriaceae . They are associated with prolonged hospital stays. Vesicoureteral reflux, previous UTI and recent antibiotic use are risk factors.